Brand image and identity : Case Lumene Oy - Helin, Sasi (Arcada - Nylands svenska yrkeshögskola, 2014)
The aim of this research was to introduce the main components and concepts of brand image, identity and brand building to the reader. As a company case the research studied the current brand image and identity of Lumene Oy in Finland. The target population of the study was young women, aged between 19-30 and living in the greater Helsinki region. The empirical research was carried on by a quantitative method. The research had three main research questions aiming to find out the brand identity of Lumene Oy, the current brand image of the firm according to the target population and if the brand identity meets with the current brand image. The research introduced the major brand strategy decisions and the brand identity structure. The brand personality scale (BPS): The Big Five and the theory of the four perspectives by David A. Aaker were presented. The results of the research were discussed in three different parts; the first part analyzed how Lumene Oy aspires to be perceived and studied the brand identity. The second part analyzed the results of the survey, and the current brand image of Lumene Oy. The third part of the discussion studied the differences between the brand identity and image by perceptual maps. Lumene Oy has succeeded in building a good relationship between value and price and the target population was satisfied with the products. Lumene was associated with personality features such as traditional, close-to-nature and arctic by the target population. There was still a slight difference between the desired brand identity and how the target population perceived the brand image as the population of the research didn’t find the brand image of Lumene Oy as extreme as what the firm has been marketing itself. Opinnäytetyön tarkoituksena oli esitellä brändi imagon, identiteetin ja brändin rakentamisen pääkomponentit ja käsitteet lukijalle. Tapaustutkimuksessa tutkittiin Lumene Oy:n tämänhetkistä brändi identiteettiä ja imagoa Suomessa. Tutkimuksen kohderyhmä oli pääkaupunkiseudulla ...